2017
DOI: 10.1002/mrm.26829
|View full text |Cite
|
Sign up to set email alerts
|

pH‐sensitive amide proton transfer effect dominates the magnetization transfer asymmetry contrast during acute ischemia—quantification of multipool contribution to in vivo CEST MRI

Abstract: The study complements recent in vivo quantitative chemical exchange saturation transfer work to shed light on the sensitivity and specificity of endogenous APT MRI to tissue acidosis. Magn Reson Med 79:1602-1608, 2018. © 2017 International Society for Magnetic Resonance in Medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 45 publications
5
57
0
Order By: Relevance
“…In addition, the guanidinium protons of creatine are known to contribute to the 2.0‐ppm CEST effect despite its relatively low concentration in brain and base‐catalyzed property . Using a multipool decoupling approach, our previous study found that the fitted guanidinium CEST effect at 2.0 ppm reduced in focal ischemic lesion . However, this finding can be limited by the less densely sampled Z‐spectrum obtained at a larger saturation power (1.5 µT) and fitted the CEST effect between 2 ppm and 3 ppm with a single exchanging pool, whereas 2 peaks (2.0 ppm and 2.75 ppm) can be clearly detected with finer spectral resolution in current study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the guanidinium protons of creatine are known to contribute to the 2.0‐ppm CEST effect despite its relatively low concentration in brain and base‐catalyzed property . Using a multipool decoupling approach, our previous study found that the fitted guanidinium CEST effect at 2.0 ppm reduced in focal ischemic lesion . However, this finding can be limited by the less densely sampled Z‐spectrum obtained at a larger saturation power (1.5 µT) and fitted the CEST effect between 2 ppm and 3 ppm with a single exchanging pool, whereas 2 peaks (2.0 ppm and 2.75 ppm) can be clearly detected with finer spectral resolution in current study.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Eq (3), the APTW signal includes not only the APTR but also MTR' asym (3.5 ppm), which is attributed to the upfield NOE effect [22]. However, a recent quantitative CEST study using animal models confirmed that the APTR accounts for a greater part of the MTR asym (3.5 ppm) changes than the NOE effect [28]. Collectively, this suggests that the APTW signal would primarily depend on tissue pH of the infarction, even in the subacute phase.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, the concentration of amide protons may vary in tumor; therefore, accurate pH values cannot be calculated. To overcome these limitations, Sun and colleagues have proposed and investigated different correction approaches to isolate the exchange rate (i.e., pH-weighted) contribution in the human brain [62][63][64][65]. On the other hand, Bartha's group set up an amine/amide concentration-independent detection method (AACID) based on a ratiometric approach [66].…”
Section: Endogenous Diacest Ph Methodsmentioning
confidence: 99%